Pengembangan Video Pembelajaran Pengantar Struktur Aljabar - Aziz, Abdul (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
The development of instructional videos for an introductory course on algebraic structures aims to improve student understanding with different learning methods. Students produce videos containing algebraic structure material, they have mastered the concept correctly. Through the preparation of making instructional videos, students are motivated to increase their knowledge regarding algebraic structure material. The method used in this research is development research that describes student learning outcomes in mastering the concept of algebraic structures. The results showed that students who could explain the algebraic structure material in the video well showed a good understanding of algebraic material. In making videos, students are motivated to present interesting work and also the concept of correct algebraic structures. Students learn from various reading sources to present the correct algebraic concepts in the form of learning videos. The content of the learning videos contains concepts and practice questions. The conclusion that can be obtained in this study is that the development of instructional videos carried out by students can help students understand the algebraic structure material, because it contains cooperative learning methods.